Evil Crystallizing in Children’s Fiction as Cultural Echoes of the 20th Century. / Cristalización del mal en la ficción infantil como ecos culturales del siglo XX . - RUKAVISHNIKOVA, OLGA; SAENKO, NATALYA; PANOVA, ELENA (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The study examines the etiology of the Evil theme in the children's literature of the late 20th — early 21st century from the sociocultural perspective.The paper outlines some of the sociocultural effects of the children's horror literature, feeding on infantilism as an emerging subculture. The study’s particular emphasis is meant on key focus areas of the children’s literature, like genre peculiarities and stylistics, which need to be “sanitized”, upon the authors’s point of view. The governing role of the State in the regulation of the publishing industry is given special consideration.RESUMEN El estudio examina la etiología del tema del Mal en la literatura infantil de finales del siglo XX y principios del XXI desde la perspectiva sociocultural. El documento describe algunos de los efectos socioculturales de la literatura de terror infantil, alimentándose del infantilismo como una subcultura emergente. El énfasis particular del estudio está destinado a áreas clave de enfoque de la literatura infantil, como las peculiaridades del género y la estilística, que deben ser "saneadas", según el punto de vista de los autores. Se presta especial atención al papel rector del Estado en la regulación de la industria editorial.